Insider Trading and Fraudulent Share Repurchase - Du Wang; Xiang Li; Hui Tang; Yicheng Sun (Credit and Capital Markets – Kredit und Kapital, 2022)
Share repurchase conveys information to investors and influences stock price in capital market. Normally when a company announces share buyback, the company's stock price will rise immediately. Thus, some insiders may take advantage of this pattern and create a fake repurchase event. When the stock price rises due to the announcement, the insiders can sell their shares at a higher price, which is insider trading of fraudulent share repurchase. We study short-term reactions around the repurchase event, using a sample of 2,272 repurchase firms in the Chinese stock market from 2013 to 2019. The main finding is that insider trading around the repurchase event is prevalent and insider trading of fraudulent repurchase is most serious. We also find that companies with more serious agency problem and poorer corporate governance are more likely to engage in fraudulent repurchase, and that companies with lower EPS and ROA, larger firm size and higher leverage are more prone to have fraudulent repurchase event. This paper can provide practical guidance in differentiating the normal repurchase from the fraudulent repurchase.
Keywords: G14; G30; 330; Fraudulent Share Repurchase; Insider Trading; Signal Theory; Agency Problem; Corporate Governance